Assessing the Impact of Different Technological Strategies on the Fate of Salmonella in Chicken Dry-Fermented Sausages by Means of Challenge Testing and Predictive Models - Anna Austrich-Comas; Anna Jofré; Pere Gou; Sara Bover-Cid (Microorganisms, 2023)
Salmonella is the main relevant pathogen in chicken dry-fermented sausages (DFS). The safety of shelf-stable DFS must rely on the production process, which should not only prevent growth but promote inactivation of Salmonella. The aim of the study was to assess the behaviour of Salmonella during the production process of two types of low-acid chicken DFS. The impact of the use of starter culture, corrective storage and high-pressure processing (HPP) at different processing times was assessed through challenge testing, i.e., inoculating a cocktail of Salmonella into the meat batter (at 6 Log10 cfu/g) used for sausage manufacture. Sausages of medium (fuet-type, FT) and small (snack-type, ST) calibre were elaborated through ripening (10–15 °C/16 d) and fermentation plus ripening (22 °C/3 d + 14 °C/7 d). Physico-chemical parameters were analysed and Salmonella was enumerated throughout the study. The observed results were compared with the simulations provided by predictive models available in the literature. In FT, a slight decrease in Salmonella was observed during the production process while in ST, a 0.9–1.4 Log10 increase occurred during the fermentation at 22 °C. Accordingly, DFS safety has to be based on the process temperature and water activity decrease, these factors can be used as inputs of predictive models based on the gamma-concept, as useful decision support tool for producers. Salmonella lethality was enhanced by combining HPP and corrective storage strategies, achieving >1 and 4 Log10 reductions for FT and ST, respectively.